A hydrothermal catalytic reforming hydrogen production catalyst carrier and its preparation method and application
By adding iron elements to the copper manganese spinel support, the Fe2O3 content is optimized, the (Fe-Cu)Mn2O4 support is formed, and Ru/CeO2 is combined as a catalyst to solve the problem of poor structural stability of the catalyst under high temperature conditions, the carbon conversion rate and hydrogen yield of biofuel are improved, and efficient and stable catalytic effect is achieved.
Patent Information
- Application Number
- CN202411240367.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-05
AI Technical Summary
In the existing hydrothermal reforming and hydrogen production technology of biofuels, the catalyst has poor structural stability under high temperature conditions, which is prone to coke accumulation, resulting in poisoning or failure, and the efficiency and long-term stability of carbon conversion and hydrogen yield are insufficient.
The spinel composite material (Fe-Cu)Mn2O4 is used as a support. By optimizing the content of Fe2O3 in the support, the catalyst's oxygen storage and oxygen release ability is improved, the anti-coking and anti-sintering properties are enhanced, and Ru/CeO2 is used as a catalyst to improve catalytic activity.
The structural stability and coking resistance of the catalyst under high temperature conditions are achieved, the carbon conversion rate and hydrogen yield of biofuels are improved, the high catalytic activity of the catalyst is maintained, and the content of short-chain gaseous hydrocarbons in hydrogen-rich synthesis gas is reduced.
Smart Images

Figure CN119098187B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biofuels, and in particular to a hydrothermal catalytic reforming hydrogen production catalyst carrier and a preparation method and application thereof, and more particularly to a reforming catalyst using a spinel-type composite material as a carrier and a preparation method thereof. Background Art
[0002] Fossil fuels, such as oil, natural gas and coal, are unsustainable non-renewable energy sources. Renewable carbon-based biomass energy sources are abundant and widely exist in daily wastes, such as livestock manure, straw, domestic garbage, sewage sludge and waste oil, with huge reserves. These biomasses can be converted and processed into biofuels to serve industrial production and daily life. An important application area of biofuels is hydrothermal catalytic reforming to produce hydrogen for use in the field of fuel cells. The basic principle is that under the action of special catalysts, the long-chain molecules in biofuels are cracked into short-chain molecules through hydrothermal reactions, while mainly releasing hydrogen and producing some by-products such as carbon monoxide, methane and carbon dioxide for fuel cell power generation. Therefore, the use of biofuels to produce hydrogen is a technical approach to efficiently utilize biomass resources, which has great social and economic value in reducing greenhouse gas emissions, alleviating energy crises and promoting carbon neutrality.
[0003] The technology of hydrothermal catalytic reforming of biofuels to produce hydrogen has been developed to date. Although there is a relatively mature production process, its popularity has always been limited by the high efficiency and long-term stability of carbon conversion rate and hydrogen yield. The reason for the difficulty in popularizing the technology is that the composition of biofuels is complex and the structural stability of the catalyst is poor under high temperature conditions, which makes it easy to produce a large amount of coke accumulation during the reforming process, resulting in catalyst poisoning or even failure. Therefore, the development of structurally stable and efficient catalysts has become an important development direction in this field. Existing reforming catalysts generally contain three components: active metals, promoters and carriers. Among them, active metals mainly include precious metals such as Rh, Ru, Pt, Pd, Re, and transition metals such as Fe, Cu, Ni, and Co. In contrast, although precious metals have higher catalytic activity, they are expensive and easily poisoned by carbon deposition; although transition metals have low cost, good reaction activity and gas selectivity, they are not resistant to high temperatures and are prone to overheating and sintering, resulting in a decrease in hydrogen yield. In addition, the carrier, as the skeleton of the catalyst, can enhance the dispersion of the active metal and increase the contact area between the active metal and the biofuel and water vapor during the catalytic reforming process, and can even provide catalytic active sites to play the role of a co-catalyst. 2 、Al 2 O 3 、ZrO 2 and CeO 2However, there are problems such as easy coking and collapse at high temperatures, which leads to a large number of active metals agglomerating and sintering. 2 Rare earth metal oxides such as MgO and alkaline earth metal oxide promoters and precious metal promoters can change the electronic structure, ion valence and active sites of the catalyst, enhance the interaction between the active metal and the carrier, improve the dispersion of the active metal on the carrier, and improve the anti-sintering and anti-coking properties of the reforming catalyst. However, simply relying on the optimization of the promoter still cannot meet the needs of practical applications. This is because the reforming catalyst is essentially a multiphase catalyst, and its ultimate catalytic activity, structural stability, and high temperature resistance are inseparable from the three main components mentioned above and their interrelationships.
[0004] In order to obtain the structural stability required by the support at high temperatures, spinel supports with high hardness and thermal stability have been verified, such as spinel NiAl 2 O 4 It can play a good anchoring role on Ni catalyst, improve the interaction between the two and the dispersion of Ni on the carrier, and improve the anti-coking performance and thermal stability of reforming catalyst. 2 O 4 In fact, the Ni in the catalyst will be completely reduced at high temperatures (~850°C), resulting in catalytic failure; in order to obtain high catalytic efficiency, various precious metal and transition metal catalysts have also been widely studied. However, the multiphase composite of metal catalysts, carriers and promoters, and how the composite three-phase reforming catalyst can simultaneously achieve structural thermal stability, sintering resistance, coking resistance, high catalytic efficiency, low-cost preparation and long service life are important issues that need to be continuously considered in the development of biofuel hydrothermal catalytic reforming hydrogen production technology. In particular, the development of high-performance carriers, because the carrier is the skeleton to which the catalyst and promoter are attached, only if the carrier has a stable structure and excellent high temperature resistance can it ensure that the metal catalyst and promoter on its surface are evenly dispersed and well combined, so that the reforming catalyst has the basic prerequisite for performance improvement. Summary of the invention
[0005] Copper manganese spinel is a low-cost, high-performance VOCs catalytic combustion catalyst, but it also faces the problem of poor anti-coking. In view of this, the present invention adds iron to the copper manganese spinel to make up for the defects of the copper manganese spinel carrier such as low oxygen loading capacity and easy coking.
[0006] In one aspect, the present invention provides a spinel reforming catalyst carrier, wherein the chemical formula of the catalyst carrier is (Fe-Cu)Mn 2 O 4 ;
[0007] According to a specific embodiment of the present invention, the (Fe-Cu)Mn 2 O 4 The molar ratio of Fe, Cu and Mn is as follows:
[0008] Fe 2 O 3 :CuO:MnO 2 It is (25-34):(16-25):100.
[0009] The Fe 2 O 3 The Fe 2 O 3 and the total molar percentage of the CuO is 50-67%;
[0010] The Fe 2 O 3 and the sum of the CuO and the MnO 2 The molar ratio is 0.5:1.
[0011] The present invention adds iron element, Fe 2 O 3 Compared with CuO and MnO 2 It has stronger oxygen storage and release capacity, making up for the defects of copper-manganese spinel carrier such as low oxygen loading capacity and easy coking.
[0012] The second aspect of the present invention provides a method for preparing (Fe-Cu)Mn 2 O 4 A method for a spinel-type reforming catalyst carrier, comprising:
[0013] A. Combine CuO, Fe 2 O 3 、MnO 2 The powders are mixed to obtain mixed powders;
[0014] B. Sintering the mixed powder in an argon atmosphere to obtain a spinel carrier (Fe-Cu)Mn 2 O 4 ,
[0015] in,
[0016] The Fe 2 O 3 , CuO, MnO 2 The molar ratio is (25-34):(16-25):100.
[0017] According to a specific embodiment of the present invention, in step A, the mixing treatment method is: CuO, Fe 2 O3 、MnO 2 The powder is sequentially subjected to ethanol dispersion treatment, grinding treatment, and drying treatment;
[0018] The grinding process lasts for 6-12 hours;
[0019] The temperature during the drying process is 70-90°C and the duration is 6-10h;
[0020] The Fe 2 O 3 The Fe 2 O 3 and the total molar percentage of the CuO is 50-67%;
[0021] The Fe 2 O 3 and the sum of the CuO and the MnO 2 The molar ratio is 0.5:1.
[0022] According to a more specific embodiment of the present invention, in the mixed powder, (CuO+Fe 2 O 3 ) and MnO 2 The molar ratio of Fe is 0.5:1, of which Fe 2 O 3 Accounting for (CuO+Fe 2 O 3 ) has a molar percentage of 50-67%.
[0023] The inventors of this application optimized Fe 2 O 3 On the support (Fe-Cu)Mn 2 O 4 The catalytic activity can be improved by increasing the content in the hydrogen-rich synthesis gas, thereby reducing the content of short-chain gaseous hydrocarbons in the hydrogen-rich synthesis gas, curbing the coking behavior on the catalyst surface from the source, and maintaining the high catalytic activity of the catalyst.
[0024] According to a specific embodiment of the present invention, in step B, the temperature of the sintering treatment is 1300-1500°C and the duration is 3-5 hours. 2 O 4 After cooling naturally, the carrier (Fe-Cu)Mn was obtained by crushing, grinding and sieving. 2 O 4 Spinel powder.
[0025] According to a specific embodiment of the present invention, the (Fe-Cu)Mn 2 O 4Compared with traditional copper-manganese spinel catalyst carriers, spinel reforming catalyst carriers have stronger oxygen storage and release capabilities and can produce excellent oxygen flow properties, thereby improving the catalytic activity of the catalyst.
[0026] The third aspect of the present invention provides the (Fe-Cu)Mn 2 O 4 Application of spinel reforming catalyst carrier in the preparation of reforming catalyst.
[0027] A fourth aspect of the present invention provides a method for preparing Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 A method for reforming a catalyst, comprising:
[0028] a. Add concentrated nitric acid and concentrated ammonia water to deionized water to obtain a mixed solution A;
[0029] b. The (Fe-Cu)Mn 2 O 4 The spinel reforming catalyst carrier is mixed with the mixed solution A, and stirred to obtain a suspension 1;
[0030] c. adding cerium nitrate hexahydrate to the suspension 1 to obtain a suspension 2;
[0031] d. Add concentrated aqueous ammonia and ethylene glycol to the suspension 2, stir at 100-110 ° C for 3-6 hours to obtain a suspension 3;
[0032] e. The suspension 3 was separated into solid and liquid by vacuum filtration to obtain a solid slurry;
[0033] f. The solid slurry was dried and then heated to 290-310 ° C and kept warm for 5-7h to obtain powder B. Ethanol was added to the powder B to dissolve and obtain a suspension 4.
[0034] g. After the ruthenium acetylacetonate is dissolved in the ethanol solution, the suspension 4 is stirred at 94-98 ° C until the solvent is completely evaporated to obtain a powder C;
[0035] h. Gradually heat powder C to 390-410℃ and keep it warm for 5-7h to obtain Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 Reforming catalyst.
[0036] The inventors of the present application optimize the Ru content in the catalyst to avoid the reduction of specific surface area and total pore volume caused by excessive loading of Ru on the catalyst surface, maintain sufficient contact between the catalyst and the fuel, and thus produce high catalytic activity.
[0037] In step b, the (Fe-Cu)Mn 2 O 4 The working concentration of the spinel reforming catalyst carrier in the suspension 1 is 0.28-0.286 g / mL;
[0038] In step c, in the suspension 2, the working concentration of the cerium nitrate hexahydrate is 0.034-0.037 g / mL;
[0039] According to a specific embodiment of the present invention, the rotation speed during stirring is 400 r / min, and the concentration of alcohol used to dissolve the substance is 75%-98%.
[0040] According to a specific embodiment of the present invention, the (Fe-Cu)Mn 2 O 4 Spinel reforming catalyst carrier, cerium nitrate hexahydrate and ruthenium acetylacetonate in the preparation of the Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 The mass ratio of the reforming catalyst input is (17151-17154):(2520-2523):(3.15-4.98).
[0041] The Ru / CeO synthesized by the present invention 2 / (Fe-Cu)Mn 2 O 4 After 72 hours of steam reforming catalysis at 900°C, the structure of the reforming catalyst remained intact, and its carbon conversion rate for biofuels remained as high as 96%. The hydrogen yield was still maintained at a high level of 86%. The content of short-chain gaseous hydrocarbons in the hydrogen-rich synthesis gas was as low as 2%, thus curbing the occurrence of coking on the catalyst surface at the source.
[0042] A fifth aspect of the present invention provides a Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 The reforming catalyst is prepared by the method described in the fourth aspect.
[0043] The sixth aspect of the present invention provides the (Fe-Cu)Mn 2 O 4 Spinel reforming catalyst carrier and the Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 Application of reforming catalysts in hydrothermal catalytic reforming to produce hydrogen.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) Synthesized (Fe-Cu)Mn 2 O 4 The carrier is resistant to high temperatures and contains Fe and Cu transition metals, which can act as a promoter;
[0046] (2) Synthesized Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 After 72 hours of steam reforming catalysis at 900°C, the structure of the reforming catalyst remained intact, and its carbon conversion rate for biofuels remained as high as 96%, and the hydrogen yield remained at a high level of 86%. The content of short-chain gaseous hydrocarbons in the hydrogen-rich synthesis gas was as low as 2%, which curbed the occurrence of coking on the catalyst surface from the source, which was conducive to maintaining the high catalytic activity of the catalyst;
[0047] (3) Synthesized Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 Ru metal catalyst and CeO on the surface of reforming catalyst 2 The promoter has high dispersibility and is compatible with (Fe-Cu)Mn 2 O 4 The carrier has strong interaction and excellent resistance to high-temperature sintering, and the metal catalyst will not agglomerate, sinter, or be reduced;
[0048] (4) (Fe-Cu)Mn 2 O 4 The carrier has a significantly improved loading capacity for Ru catalysts and can also maintain high dispersion of Ru on its surface;
[0049] (5) Synthesized (Fe-Cu)Mn 2 O 4 The carrier has both Fe 2 O 3 , Mn 2 O 3 The excellent properties of CuO make up for the defects of single metal oxide carriers such as low oxygen loading capacity and easy coking, and synergistically produce high reforming catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0051] Figure 1In one embodiment of the present invention, Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 Metallographic microscopic images (ac) and statistical analysis of particle size distribution (d) of reforming catalyst, where: Figure 1 The scale bar in (a) is 500 μm. Figure 1 The scale bar in (b) is 200 μm. Figure 1 The scale bar in (c) is 50 μm;
[0052] Figure 2 In one embodiment of the present invention, Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 Scanning electron microscope (SEM) image of the reforming catalyst, scale bar is 500 nm;
[0053] Figure 3 In one embodiment of the present invention, Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 Scanning electron microscope (SEM) images of the reforming catalyst and their element distribution diagram, where the scale of the SEM image is 2.5 μm;
[0054] Figure 4 In one embodiment of the present invention, (Fe-Cu)Mn 2 O 4 Support and Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 XRD pattern of reforming catalyst;
[0055] Figure 5 This is a flow chart of a reforming hydrogen production device in one embodiment of the present invention.
[0056] Figure 6 The carbon conversion rate and hydrogen yield bar graph of the catalysts prepared in Examples 1-3 and Comparative Examples 1-2 after catalytic reforming ( Figure 6 a), and the bar chart of the relative percentage content of each component in the hydrogen-rich synthesis gas ( Figure 6 b) in the above;
[0057] Figure 7 The carbon conversion rate and hydrogen yield bar graph of the catalysts prepared in Example 2, Example 4, Example 5 and Comparative Example 3 after catalytic reforming ( Figure 7 a), and the relative percentage content of each component in the hydrogen-rich synthesis gas ( Figure 7 b) in the above;
[0058] Figure 8A comparison chart of specific surface area and total pore volume of catalysts prepared in Example 2, Example 4, Example 5 and Comparative Example 3 of the present invention;
[0059] Fig. 9 This is a comparative test of the catalytic activity and thermal stability of the catalysts in Examples 1-5 of the present invention and Comparative Examples 1-2, wherein: Fig. 9 The a carbon conversion rate line chart in Fig. 9 b in FIG. 1 is a line graph of hydrogen yield. DETAILED DESCRIPTION
[0060] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0061] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0062] In this document, the terms “contain”, “include” or “comprise” are open expressions, that is, they include the contents specified in the present invention but do not exclude other contents.
[0063] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0064] In the present invention, Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 With Ru@CeO 2 @(Fe-Cu)Mn 2 O 4 Synonymous, "@" represents a payload.
[0065] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention provides drawings, which are part of the disclosure of the present invention. They are mainly used to illustrate the embodiments and can be used in conjunction with the relevant descriptions in the specification to explain the operating principles of the embodiments. By referring to these contents, ordinary technicians in this field should be able to understand other possible implementation methods and advantages of the present invention.
[0066] In the present application, the specific surface area and total pore volume of the catalyst are measured by a fully automatic BET specific surface (area) analysis tester; the components in the hydrogen-rich synthesis gas after catalytic reforming, as well as the relative percentage content of each component, the carbon conversion rate and the hydrogen yield are all measured by a high-performance gas chromatograph.
[0067] The purchase sources and product numbers of the reagents used in the examples of this application are shown in Table 1:
[0068] Table 1
[0069] name Manufacturer Product Number <![CDATA[Fe 2 THE 3 ]]> Shanghai MacLean Biochemical Technology Co., Ltd. F923195 CuO Shanghai MacLean Biochemical Technology Co., Ltd. C835833 <![CDATA[MnO 2 ]]> Shanghai MacLean Biochemical Technology Co., Ltd. M813969 Ethanol Shanghai MacLean Biochemical Technology Co., Ltd. E766256 Concentrated ammonia Shanghai MacLean Biochemical Technology Co., Ltd. A765779 Ethylene glycol Shanghai MacLean Biochemical Technology Co., Ltd. E808735 Cerium nitrate hexahydrate Shanghai MacLean Biochemical Technology Co., Ltd. C804686 Ruthenium acetylacetonate Shanghai MacLean Biochemical Technology Co., Ltd. R795404
[0070] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product instructions are used. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the art without making creative work are within the scope of protection of the present invention.
[0071] Example 1
[0072] a. Preparation of carrier:
[0073] According to (CuO+Fe 2 O 3 ) and MnO 2 The molar ratio of Fe is 0.5:1, of which Fe 2 O 3 Accounting for (CuO+Fe 2 O 3 ) is 50% by mole. Powder raw materials are weighed with an electronic balance, poured into a ball mill, and then ethanol is added to fully disperse the powder and then placed in a ball mill for 8 hours. Subsequently, the powder is transferred to an oven and dried at 80°C for 8 hours. The dried powder is crushed and poured into an alumina crucible, flattened, and sintered in an argon atmosphere. The sintering temperature is 1400°C and the heat preservation time is 4 hours. After natural cooling, the powder is crushed and ground, and passed through a 300-mesh sieve to obtain the carrier (Fe-Cu)Mn 2 O 4 Spinel powder.
[0074] b. Preparation of reforming catalyst:
[0075] (b1) Take a 1-liter beaker and add 500 mL of deionized water. Take 1 mL of concentrated nitric acid (purchased from Linyi Luguang Chemical Co., Ltd.) and add it dropwise into the deionized water, stirring evenly with a glass rod. Then, take 2 mL of concentrated ammonia water and add it dropwise into the above solution, stirring evenly to prepare mixed solution A.
[0076] (b2) Take a 150 mL beaker and take 17.1534 g of the carrier (Fe-Cu)Mn 2 O 4 The spinel powder was poured into a beaker, and 60 mL of the mixed solution A prepared above was added, and it was magnetically stirred at a speed of 400 r / min to form a suspension; then, 2.5210 g of cerium nitrate hexahydrate was weighed, dissolved in 10 mL of deionized water, and slowly added dropwise to the suspension; then, 1 mL of concentrated ammonia water was taken and slowly added dropwise to the suspension, and magnetically stirred at 400 r / min for 15 min; then, 30 mL of ethylene glycol was poured into it, and it was transferred to an oil bath, heated to 105°C, and kept warm for 4 hours under magnetic stirring at 400 r / min to terminate the reaction.
[0077] (b3) The suspension obtained in the reaction of b2 was subjected to liquid-solid separation by vacuum filtration; the obtained solid slurry was dried at 80°C; then, the dried powder was transferred to a muffle furnace, the temperature was increased to 300°C at 2°C / min, and the temperature was kept for 6 hours and then naturally cooled to obtain powder B.
[0078] (b4) Powder B in b3 was transferred to a 150 mL beaker, and 60 mL of ethanol was added and stirred magnetically to form a suspension; then, 4.98 mg of ruthenium acetylacetonate (C 15 H 21 O 6 Ru) was poured into a 50 mL beaker, and 25 mL of ethanol was added and stirred until fully dissolved; then, C 15 H 21 O 6 The Ru ethanol solution was added dropwise to the ethanol suspension of powder B, and magnetic stirring was carried out at 95 °C and 400 r / min for 6 h until the solvent in the beaker was completely evaporated; finally, the dried powder obtained after evaporation was transferred to a muffle furnace, heated to 400 °C at 2 °C / min, and kept at this temperature for 6 h before cooling naturally to obtain Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 Reforming catalyst.
[0079] The Ru / CeO prepared in Example 1 2 / (Fe-Cu)Mn 2 O 4 The reforming catalyst was imaged by metallographic microscope and the particle size distribution was statistically analyzed. The results are as follows Figure 1 As shown, the particle size of the reforming catalyst powder synthesized in this example is mainly distributed in the range of 30-90 μm.
[0080] The Ru / CeO prepared in Example 12 / (Fe-Cu)Mn 2 O 4 The reforming catalyst was imaged by scanning electron microscope. Figure 2 As shown, (Fe-Cu)Mn 2 O 4 A large amount of Ru / CeO is densely attached to the surface of the carrier. 2 Particles.
[0081] Example 2
[0082] Compared with Example 1, the difference of the embodiment is that Fe 2 O 3 Accounting for (CuO+Fe 2 O 3 The conditions for producing hydrogen by steam catalytic reforming of biomass fuel are the same as those in Example 1.
[0083] The Ru / CeO prepared in Example 2 2 / (Fe-Cu)Mn 2 O 4 The reforming catalyst was scanned by a scanning electron microscope to obtain a scanning electron microscope image and an element distribution map. The results are as follows: Figure 3 As shown, it shows that the Ru element is evenly and densely distributed in the CeO 2 The surface of the particles, Fe and Cu elements are loaded with a large amount of Ru / CeO 2 Although it is difficult to observe the surface element analysis test by SEM, the presence of Fe and Cu elements can still be detected.
[0084] The (Fe-Cu)Mn prepared in Example 2 2 O 4 Support and Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 The reforming catalyst was subjected to X-ray diffraction analysis, and the results were as follows Figure 4 As shown, the synthesized (Fe-Cu)Mn 2 O 4 The carrier is a spinel crystal, the synthesized Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 The XRD spectrum of the reforming catalyst has additional Ru / CeO 2 The crystallization peak (the peak marked by the black square in the figure).
[0085] Example 3
[0086] Compared with Example 1, the difference of the embodiment is that Fe2 O 3 Accounting for (CuO+Fe 2 O 3 The conditions for producing hydrogen by steam catalytic reforming of biomass fuel are the same as those in Example 1.
[0087] Example 4
[0088] Compared with Example 2, the difference of the embodiment is that ruthenium acetylacetonate (C 15 H 21 O 6 The conditions for producing hydrogen by steam catalytic reforming of biomass fuel are the same as those in Example 1.
[0089] Example 5
[0090] Compared with Example 2, the difference of the embodiment is that ruthenium acetylacetonate (C 15 H 21 O 6 The dosage of Ru) is 4.06 mg, and the rest are the same. The conditions for producing hydrogen by steam catalytic reforming of biomass fuel are the same as those in Example 1.
[0091] Comparative Example 1
[0092] Compared with Example 1, the difference of the embodiment is that Fe 2 O 3 Accounting for (CuO+Fe 2 O 3 The conditions for producing hydrogen by steam catalytic reforming of biomass fuel are the same as those in Example 1.
[0093] Comparative Example 2
[0094] Compared with Example 1, the difference of the embodiment is that Fe 2 O 3 Accounting for (CuO+Fe 2 O 3 The conditions for producing hydrogen by steam catalytic reforming of biomass fuel are the same as those in Example 1.
[0095] Comparative Example 3
[0096] Compared with Example 2, the difference of the embodiment is that ruthenium acetylacetonate (C 15 H 21 O 6 The dosage of Ru) is 5.11 mg, and the rest are the same. The conditions for producing hydrogen by steam catalytic reforming of biomass fuel are the same as those in Example 1.
[0097] Hydrogen production from steam catalytic reforming of biomass fuels:
[0098] The reforming catalysts prepared in Examples 1-5 and Comparative Examples 1-4 were used in Figure 5 In the reforming hydrogen production process shown, the selected biomass fuel is a representative extract of Scots pine powder, which can be obtained by sealing microwave heating assisted hydrothermal treatment of Scots pine powder and then filtering. The control conditions of the steam catalytic reforming hydrogen production process of biomass fuel are as follows: the reaction space velocity is controlled to be 20000h -1 The reforming temperature in the reactor is 900°C, the reforming pressure is 1 atm, the molar ratio of water vapor to C element in the fuel is 6:1, and the reaction time is 10 h.
[0099] The carbon conversion rate and hydrogen yield of the catalysts prepared in Examples 1-3 and Comparative Examples 1-2 after catalytic reforming, as well as the relative percentage content of each component in the hydrogen-rich synthesis gas, were measured. The results are as follows: Figure 6 As shown, Figure 6 a in the figure is the carbon conversion rate and hydrogen yield of the catalyst after catalytic reforming, which shows that when Fe 2 O 3 When the molar content of Fe is within the range of 50% to 67% (Examples 1-3), the carbon conversion rate and hydrogen yield that the catalyst can produce will increase with the increase of Fe 2 O 3 The content of Fe 2 O 3 When the content is 0 (Comparative Example 1), the carbon conversion rate and hydrogen yield are significantly lower than those of Examples 1-3; however, when Fe 2 O 3 When the content is 70% (Comparative Example 2), the carbon conversion rate and hydrogen yield are higher than those of Examples 1-3. 2 O 3 The reason why the carbon conversion rate and hydrogen yield increase with the increase of the proportion of (Fe-Cu)Mn in the catalyst carrier is that 2 O 4 The composite carrier is rich in oxygen species, among which Fe 2 O 3 Compared with CuO and MnO 2 It has stronger oxygen storage and release capacity, can produce excellent oxygen flow performance, and thus produce gradually improved catalytic activity; Figure 6 b in the figure is the component analysis of hydrogen-rich syngas. The results show that the components of hydrogen-rich syngas mainly include H 2 ,CO,CO 2 , CH 4 and other short-chain gaseous hydrocarbons, H 2The higher the percentage, the higher the catalytic efficiency. The greater the percentage of short-chain gaseous hydrocarbons, the greater the risk of coking on the catalyst surface. 2 The percentage is the lowest (61%), and the content of short-chain gaseous hydrocarbons is as high as 19%. These short-chain gaseous hydrocarbons are the main factors of coking in the reforming process. If their content is too high, it is very easy to cause coking on the catalyst surface, hindering the effective contact between the catalyst and the fuel, and causing catalyst poisoning. In addition, Examples 1-3 all showed very similar levels of carbon conversion and hydrogen yield, but the proportion of short-chain gaseous hydrocarbons in Example 2 was the lowest among the three (2%), which means that the comprehensive performance of the catalyst in Example 2 in terms of anti-coking performance and catalytic activity is the best. Although Fe 2 O 3 The H content of the hydrogen-rich synthesis gas in Comparative Example 2 is the highest. 2 The percentage is as high as 87%, but the content of short-chain gaseous hydrocarbons is also as high as 11%, which is significantly higher than that of Examples 1-3. The above comparative analysis of catalytic performance shows that (Fe-Cu)Mn 2 O 4 Fe in composite carrier 2 O 3 The increase of Fe content is helpful to improve the catalytic performance of the catalyst, but too high Fe 2 O 3 The content may cause coking on the catalyst surface.
[0100] (Fe-Cu)Mn determined in Example 2 2 O 4 Fe in composite carrier 2 O 3 Based on the content, the study of ruthenium acetylacetonate (C 15 H 21 O 6 The effect of the dosage of Ru) on the catalytic activity was measured, and the carbon conversion rate and hydrogen yield of the catalysts prepared in Example 2, Example 4, Example 5 and Comparative Example 3 after catalytic reforming, as well as the relative percentage content of each component in the hydrogen-rich synthesis gas were measured. The results are shown in Figure 7 As shown, with the addition of ruthenium acetylacetonate (C 15 H 21 O 6 Ru) dosage gradually increased, Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 The Ru content in the reforming catalyst will inevitably increase gradually, resulting in changes in catalytic activity. As the Ru content gradually increases, the carbon conversion rate and hydrogen yield will gradually increase, so that in Example 2, the carbon conversion rate is as high as 96%, the hydrogen yield is as high as 86%, and the H in the hydrogen-rich synthesis gas is2 The percentage is as high as 81%. This shows that in Example 4, Example 5 and Example 2, the loading of Ru is an effective process, and Ru can be supported by CeO 2 In (Fe-Cu)Mn 2 O 4 The composite support is fully dispersed and firmly bonded, so as to give full play to the catalytic activity of the catalyst. 15 H 21 O 6 When the dosage of Ru) continued to increase to 5.11 mg (Comparative Example 3), the carbon conversion rate and hydrogen yield in Comparative Example 3 decreased sharply compared with Example 2. The inventors speculated that the excessive loading of Ru caused Ru to enter the pores inside the catalyst, causing pore blockage and resulting in the Ru / CeO 2 / (Fe-Cu)Mn 2 O 4 The specific surface area and pore volume of the reforming catalyst are sharply reduced, thereby reducing the catalytic activity of the catalyst.
[0101] The inventors further measured the specific surface area and total pore volume of the catalysts prepared in Example 2, Example 4, Example 5 and Comparative Example 3. The results are as follows: Figure 8 As shown in the figure, it is shown that as the Ru loading gradually increases (in Example 4, Example 5 and Example 2, respectively), the specific surface area and total pore volume of the corresponding catalysts do not change much and are maintained at a high level. However, when the Ru loading is too high (Comparative Example 3), the specific surface area and total pore volume of the catalyst in Comparative Example 3 are reduced to 73m 2 / g and 0.369cm 3 The reason for the sharp decrease in the specific surface area and total pore volume of the catalyst is that the excessive loading of Ru causes Ru to enter the internal pores of the catalyst, causing pore blockage.
[0102] Comparative test of thermal stability of catalytic performance: The reforming catalysts synthesized in Examples 1-5 and Comparative Examples 1-2 were subjected to continuous reaction for 72 hours under the process control conditions of steam catalytic reforming of biomass fuel to produce hydrogen in the examples, and the changes in carbon conversion rate and hydrogen yield of each catalyst were compared and analyzed. The results are shown in Fig. 9 As shown in the figure, the carbon conversion rate and hydrogen yield of Example 2 fluctuate less and can be maintained at high levels of about 96% and 86% respectively; the carbon conversion rate and hydrogen yield in Example 1 and Examples 3-5 can also be maintained near their initial levels; this shows that the catalytic activity of the catalysts in Examples 1-5 can be stably present for a long time, which is due to the spinel (Fe-Cu)Mn 2 O 4High efficiency thermal stability of the composite carrier. However, in comparison, the carbon conversion rate and hydrogen yield in Comparative Example 1 began to gradually decrease after 20 hours, and the carbon conversion rate and hydrogen yield in Comparative Example 2 began to gradually decrease after 40 hours, which is closely related to the property that the catalyst surface is easy to coke.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A spinel reforming catalyst carrier, characterized in that: The chemical formula is (Fe-Cu)Mn2O4; the molar ratio of Fe, Cu and Mn in the (Fe-Cu)Mn2O4 converted into oxides is as follows: Fe2O3:CuO:MnO2 is (25-34):(16-25):
100.
2. A method for preparing a (Fe-Cu)Mn2O4 spinel reforming catalyst carrier, characterized in that: include: A. mixing CuO, Fe2O3 and MnO2 powders to obtain mixed powder; B. sintering the mixed powder in an argon atmosphere to obtain a spinel carrier (Fe-Cu)Mn2O4, in, The molar ratio of Fe2O3, CuO and MnO2 is (25-34):(16-25):
100.
3. The method according to claim 2, characterized in that In step A, the mixing treatment method is: CuO, Fe2O3, and MnO2 powders are sequentially subjected to ethanol dispersion treatment, grinding treatment, and drying treatment; The grinding process lasts for 6-12 hours; The temperature during the drying process is 70-90°C and the duration is 6-10h; The molar percentage of the Fe2O3 in the total of the Fe2O3 and the CuO is 50-67%; The molar ratio of the sum of the Fe2O3 and the CuO to the MnO2 is 0.5:1; In step B, the sintering process is carried out at a temperature of 1300-1500° C. for 3-5 hours.
4. Use of the (Fe-Cu)Mn2O4 spinel reforming catalyst carrier according to claim 1 in the preparation of reforming catalysts.
5. A method for preparing a Ru / CeO2 / (Fe-Cu)Mn2O4 reforming catalyst, characterized in that: include: a. Add concentrated nitric acid and concentrated ammonia water to deionized water to obtain a mixed solution A; b. The (Fe-Cu)Mn2O4 spinel reforming catalyst carrier according to claim 1 is mixed with the mixed solution A and stirred to obtain a suspension 1; c. adding cerium nitrate hexahydrate to the suspension 1 to obtain a suspension 2; d. Add concentrated aqueous ammonia and ethylene glycol to the suspension 2, stir at 100-110 ° C for 3-6 hours to obtain a suspension 3; e. The suspension 3 was separated into solid and liquid by vacuum filtration to obtain a solid slurry; f. The solid slurry was dried and then heated to 290-310 ° C and kept warm for 5-7h to obtain powder B. Ethanol was added to the powder B to dissolve and obtain a suspension 4. g. After the ruthenium acetylacetonate is dissolved in the ethanol solution, the suspension 4 is stirred at 94-98 ° C until the solvent is completely evaporated to obtain a powder C; h. The powder C was heated to 390-410°C and then kept warm for 5-7h to obtain a Ru / CeO2 / (Fe-Cu)Mn2O4 reforming catalyst; The mass ratio of the (Fe-Cu)Mn2O4 spinel reforming catalyst carrier, cerium nitrate hexahydrate and ruthenium acetylacetonate added in the preparation of the Ru / CeO2 / (Fe-Cu)Mn2O4 reforming catalyst is (17151-17154):(2520-2523):(3.15-4.98).
6. The method according to claim 5, characterized in that In step b, the working concentration of the (Fe-Cu)Mn2O4 spinel reforming catalyst carrier in the suspension 1 is 0.28-0.286 g / mL; In step c, in the suspension 2, the working concentration of the cerium nitrate hexahydrate is 0.034-0.037 g / mL.
7. A Ru / CeO2 / (Fe-Cu)Mn2O4 reforming catalyst, characterized in that: Prepared by the method described in any one of claims 5-6.
8. Use of the (Fe-Cu)Mn2O4 spinel reforming catalyst carrier according to claim 1 and the Ru / CeO2 / (Fe-Cu)Mn2O4 reforming catalyst according to claim 7 in hydrothermal catalytic reforming to produce hydrogen.
Citation Information
Patent Citations
Spinel-supported catalyst for dry reforming of coke oven gas and preparation method thereof
CN103599785A
Preparation method of normal-temperature high-radiance infrared radiation ceramic material
CN112898005A